Virulence factors among enterococci isolated from traditional fermented meat products produced in the North of Portugal - Barbosa, J. (2011)
The aim of this work was to characterize Enterococcus spp. isolated from Alheira, Chouriça de Vinhais and Salpicão de Vinhais, fermented meat products produced in the North of Portugal, concerning their potential pathogenicity. One hundred and eighty two isolates (76 identified as Enterococcus faecalis, 44 as Enterococcus faecium, 1 as Enterococcus casseliflavus and 61 as Enterococcus spp.) were studied. Twenty six percent of isolates were gelatinase producers. None of the isolates produced lipase nor DNase activities. Hemolytic activity using sheep and human blood from two types (A and O) was assessed. One isolate was b-hemolytic in human blood. Results obtained in sheep blood were quite different from those obtained in human blood. Biofilm production in batch and in fed-batch mode was evaluated. In batch mode, only 28.0% and 3.9% of isolates were classified as moderate and strong biofilm producers, respectively, and in fed-batch mode, 35.7% and 63.2% of isolates were classified as moderate and strong biofilm producers, respectively. The presence of 13 virulence genes (efaAfs, efaAfm, esp, agg, cylM, cylB, cylA, cylLL cylLs and gelE) were investigated by PCR. The majority of enterococcal isolates showed the presence of one or more virulence factors, the most frequent genotype being efaAfs+ gelE+ agg+ (41.5%). E. faecalis isolates harbored multiple virulence traits, while E. faecium isolates were generally free of virulence determinants. Phenotypic and genotypic evidence of potential virulence factors were identified in Enterococcus spp. isolates, which is a reason of concern.